Marion County (Oregon) Youth Study, 1964-1979 - Polk, Kenneth ([Verlag nicht ermittelbar], 1985)
For this investigation of young men in Marion County, Oregon, subjects were interviewed in a 12-wave panel study beginning in their sophomore years of high school and continuing to age 30. The study sought to account for what happened as these individuals came of age. The research was concerned primarily with how success, trouble, and delinquency in the high school years exert an influence in later life careers. The first wave, conducted in the respondents' sophomore years of high school in 1964, consisted of a 200-item questionnaire. The second wave, the first in the longitudinal design, consisted of face-to-face interviews using a 225-item instrument during the senior year of high school. The ten subsequent waves of the study were conducted by mail, at nearly one-year intervals. The interview schedules are concerned with the issues of coming of age, such as family relations, school performance, educational plans, dating, drinking, drug use, military service, delinquency, offenses and dispositions (civilian and military), and Vietnam experiences.